2015
DOI: 10.1103/physrevd.91.063530
|View full text |Cite
|
Sign up to set email alerts
|

Probing the imprint of interacting dark energy on very large scales

Abstract: The observed galaxy power spectrum acquires relativistic corrections from lightcone effects, and these corrections grow on very large scales. Future galaxy surveys in optical, infrared and radio bands will probe increasingly large wavelength modes and reach higher redshifts. In order to exploit the new data on large scales, an accurate analysis requires inclusion of the relativistic effects. This is especially the case for primordial non-Gaussianity and for extending tests of dark energy models to horizon scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 100 publications
(71 reference statements)
1
43
0
Order By: Relevance
“…IV, baryons, DM and DE interact only indirectly by gravitation (via the Poisson equation). However, DE may interact with DM non-gravitationally, via a reciprocal exchange of energy and momentum; thus, is called interacting DE (IDE) [7,73,[109][110][111]. In this section we probe the magnification angular power spectrum for an IDE scenario-assuming (hereafter) a latetime universe dominated by DM and DE only.…”
Section: The Power Spectrum With Interacting Dark Energymentioning
confidence: 99%
See 2 more Smart Citations
“…IV, baryons, DM and DE interact only indirectly by gravitation (via the Poisson equation). However, DE may interact with DM non-gravitationally, via a reciprocal exchange of energy and momentum; thus, is called interacting DE (IDE) [7,73,[109][110][111]. In this section we probe the magnification angular power spectrum for an IDE scenario-assuming (hereafter) a latetime universe dominated by DM and DE only.…”
Section: The Power Spectrum With Interacting Dark Energymentioning
confidence: 99%
“…Note that, apart from [7,73,109], it is common in the literature to use an energy density transfer rate of the form Q ∝ a −1 Hρ x , with the main motivation being that the background energy conservation equations are easily solved. However, the Hubble rate H is typically not perturbed-being a background parameter-which is thus a problem for the perturbed case of the given transfer rate.…”
Section: A the Ide Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently shown that the local and integrated relativistic contributions can become significant on very large scales [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Here we will investigate in detail the behaviour of the integrated terms for different cases, assuming a ΛCDM model.…”
Section: Introductionmentioning
confidence: 99%
“…The need to include geometrical and lightcone effects in the theoretical modeling has been long recognised (see the seminal works [16][17][18][19][20][21]). More recently, geometrical and relativistic effects have been intensively analyzed, as it becomes clear that future surveys will need very precise modeling [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%